The Doctrine of Justification in the Theology of Juan de Valdes (1500?-1541) - Relacion, Domingo R. (My University, 1970)
A historico-doctrinal analysis or the doctrine of justification in the theology of Juan de Valdes, a Spanish Reformer of the sixteenth Century. The present study is an attempt to investigate the rich historical and cultural background out of which Valdes came and to delineate the various phases in the development and structure of his thought on justification.
In the lengthy biographical account of Valdes, we shall indicate the highlights of his early life in Spain, is education at the University of Alcala and his literary activity during the last years of his life. To locate Valdesian thinking within the stream of both Protestant and Catholic traditions, we shall present a comparative analysis of his doctrine in relation to that of Luther, Calvin and the Council of Trent. In conclusion, personal reflections on the major points discussed will be given.
Keywords: Religion; Religion